Three “R” Concept in Waste Management for Sustainable Environment - Pandiyarajan, V; Neelakantan, T.R.; Sridharan, Shasi Anand; Ramrao, Nagaraj (Journal of Sustainability Perspectives, 2022)
The dawn of the 21st century has thrown several challenges to mankind. The most dangerous among the challenges is the maintenance of a sustainable environment. While anthropogenic activities are considered as the predominant cause for environmental pollution, the solution also lies with human beings only. Here comes the role of the Three “R” concept which has been widely adopted across the globe. The Three “R” concept talks about Reducing the waste, Reusing the waste, and Recycling the waste and products to the extent possible. Today, a developing country like India generates a huge amount of solid waste, sewage, electronic waste, and gaseous pollutants.  When we adopt this Three “R” Concept, the ill effects of the pollution caused by these agents can be effectively mitigated.  Indeed, the various pollution control bodies of the governments are vigorously propagating the Three “R“ concept among the highly polluting industries to bring down the carbon emission to the sustainable level. Indeed, this is one of the United Nations Sustainable Development Goals (UNSDG). This new paradigm will definitely yield the desired result in developing and maintaining a sustainable environment which ensures the availability of pristine natural resources for the generations to come. The Higher Educational Institutions (HEI) play an important role in sustainability promotion in society. Waste management is one of the challenges educational institutions have to face in accomplishing the sustainability goals. KARE adopts the Three “R” Concepts in managing the solid, liquid, biochemical, and e-waste resulting in the development of a sustainable and eco-friendly environment on the campus. This poster details the recycling of solid, liquid, biochemical, and e-waste on Kalasalingam University campus. The solid wastes generated are converted into wealth and reused in the form of Vermicompost which is eco-friendly, the liquid waste is reused after treatment, paper and e-waste are recycled or reused through vendors. Further, the bio-medical/biochemical wastes are disposed of as per the government norms. Keyword: Reduce, Reuse, Recycle, Sustainable Development Goals (SDG), Eco-friendly